Hierarchical System for Word Discovery Exploiting DTW-Based Initialization - Walter, Oliver; Korthals, Timo; Haeb-Umbach, Reinhold; Raj, Bhiksha (Automatic Speech Recognition and Understanding Workshop (ASRU 2013))

A Novel Initialization Method for Unsupervised Learning of Acoustic Patterns in Speech (FGNT-2013-01) - Walter, Oliver; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold
In this paper we present a novel initialization method for unsupervised learning of acoustic patterns in recordings of continuous speech. The pattern discovery task is solved by dynamic time warping whose performance we improve by a smart starting point selection. This enables a more accurate discovery of patterns compared to conventional approaches. After graph-based clustering the patterns are employed for training hidden Markov models for an unsupervised speech acquisition. By iterating between model training and decoding in an EM-like framework the word accuracy is continuously improved. On the TIDIGITS corpus we achieve a word error rate of about 13 percent by the proposed unsupervised pattern discovery approach, which neither assumes knowledge of the acoustic units nor of the labels of the training data.

One Bad Apple: Backwards Compatibility Attacks on State-of-the-Art Cryptography - Jager, Tibor; Paterson, Kenneth G.; Somorovsky, Juraj (20th Annual Network and Distributed System Security Symposium, NDSS 2013, San Diego, California, USA, February 24-27, 2013)

Book review: Christoph Schubert (2009). 'Raumkonstitution durch Sprache: Blickführung, Bildschemata und Kohäsion in Deskriptionssequenzen englischer Texte.' Tübingen: Max Niemeyer - Mildorf, Jarmila (Informationsmittel für Bibliotheken)

Attention and the Speed of Information Processing: Posterior Entry for Unattended Stimuli Instead of Prior Entry for Attended Stimuli - Weiß, Katharina; Hilkenmeier, Frederic; Scharlau, Ingrid (PLoS ONE)
Why are nearly simultaneous stimuli frequently perceived in reversed order? The origin of errors in temporal judgments is a question older than experimental psychology itself. One of the earliest suspects is attention. According to the concept of prior entry, attention accelerates attended stimuli; thus they have “prior entry” to perceptive processing stages, including consciousness. Although latency advantages for attended stimuli have been revealed in psychophysical studies many times, these measures (e.g. temporal order judgments, simultaneity judgments) cannot test the prior-entry hypothesis completely. Since they assess latency differences between an attended and an unattended stimulus, they cannot distinguish between faster processing of attended stimuli and slower processing of unattended stimuli. Therefore, we present a novel paradigm providing separate estimates for processing advantages respectively disadvantages of attended and unattended stimuli. We found that deceleration of unattended stimuli contributes more strongly to the prior-entry illusion than acceleration of attended stimuli. Thus, in the temporal domain, attention fulfills its selective function primarily by deceleration of unattended stimuli. That means it is actually posterior entry, not prior entry which accounts for the largest part of the effect.

DoA-Based Microphone Array Position Self-Calibration Using Circular Statistic - Jacob, Florian; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (38th International Conference on Acoustics, Speech, and Signal Processing (ICASSP 2013))
In this paper we propose an approach to retrieve the absolute geometry of an acoustic sensor network, consisting of spatially distributed microphone arrays, from reverberant speech input. The calibration relies on direction of arrival measurements of the individual arrays. The proposed calibration algorithm is derived from a maximum-likelihood approach employing circular statistics. Since a sensor node consists of a microphone array with known intra-array geometry, we are able to obtain an absolute geometry estimate, including angles and distances. Simulation results demonstrate the effectiveness of the approach.
Keywords: Geometry calibration; microphone arrays; position self-calibration

Sampling Rate Synchronisation in Acoustic Sensor Networks with a Pre-Trained Clock Skew Error Model - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (21th European Signal Processing Conference (EUSIPCO 2013))
In this paper we present a combined hardware/software approach for synchronizing the sampling clocks of an acoustic sensor network. A first clock frequency offset estimate is obtained by a time stamp exchange protocol with a low data rate and computational requirements. The estimate is then postprocessed by a Kalman filter which exploits the specific properties of the statistics of the frequency offset estimation error. In long term experiments the deviation between the sampling oscillators of two sensor nodes never exceeded half a sample with a wired and with a wireless link between the nodes. The achieved precision enables the estimation of time difference of arrival values across different hardware devices without sharing a common sampling hardware.
Keywords: synchronization; acoustic sensor network

CuO and Co3O4 Nanoparticles: Synthesis, Characterizations, and Raman Spectroscopy - Rashad, M.; Rüsing, Michael; Berth, Gerhard; Lischka, K.; Pawlis, A. (Journal of Nanomaterials)
Copper oxide and cobalt oxide (CuO, Co3O4) nanocrystals (NCs) have been successfully prepared in a short time using microwave irradiation without any postannealing treatment. Both kinds of nanocrystals (NCs) have been prepared using copper nitrate and cobalt nitrate as the starting materials and distilled water as the solvent. The resulted powders of nanocrystals (NCs) were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and atomic force microscopy (AFM) measurements. The obtained results confirm the presence of the both of oxides nanopowders produced during chemical precipitation using microwave irradiation. A strong emission under UV excitation is obtained from the prepared CuO and Co3O4 nanoparticles. The results show that the nanoparticles have high dispersion and narrow size distribution. The line scans of atomic force microscopy (AFM) images of the nanocrystals (NCs) sprayed on GaAs substrates confirm the results of both X-ray diffraction and transmission electron microscopy. Furthermore, vibrational studies have been carried out using Raman spectroscopic technique. Specific Raman peaks have been observed in the CuO and Co3O4 nanostructures, and the full width at half maximum (FWHM) of the peaks indicates a small particle size of the nanocrystals.
Keywords: General Materials Science

Server based indoor navigation using RSSI and inertial sensor information - Hoang, Manh Kha; Schmitz, Sarah; Drueke, Christian; Vu, Dang Hai Tran; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Positioning Navigation and Communication (WPNC), 2013 10th Workshop on)
In this paper we present a system for indoor navigation based on received signal strength index information of Wireless-LAN access points and relative position estimates. The relative position information is gathered from inertial smartphone sensors using a step detection and an orientation estimate. Our map data is hosted on a server employing a map renderer and a SQL database. The database includes a complete multilevel office building, within which the user can navigate. During navigation, the client retrieves the position estimate from the server, together with the corresponding map tiles to visualize the user's position on the smartphone display.
Keywords: SQL; navigation; smart phones; wireless LAN; RSSI; SQL database; complete multilevel office building; inertial sensor information; inertial smartphone sensors; map renderer; received signal strength index information; relative position estimates; server based indoor navigation; step detection; wireless-LAN access points; Smartphone; fingerprint; indoor navigation; map tile

A Hidden Markov Model for Indoor User Tracking Based on WiFi Fingerprinting and Step Detection - Hoang, Manh Kha; Schmalenstroeer, Joerg; Drueke, Christian; Tran Vu, Dang Hai; Haeb-Umbach, Reinhold (21th European Signal Processing Conference (EUSIPCO 2013))
In this paper we present a modified hidden Markov model (HMM) for the fusion of received signal strength index (RSSI) information of WiFi access points and relative position information which is obtained from the inertial sensors of a smartphone for indoor positioning. Since the states of the HMM represent the potential user locations, their number determines the quantization error introduced by discretizing the allowable user positions through the use of the HMM. To reduce this quantization error we introduce â??pseudoâ?? states, whose emission probability, which models the RSSI measurements at this location, is synthesized from those of the neighboring states of which a Gaussian emission probability has been estimated during the training phase. The experimental results demonstrate the effectiveness of this approach. By introducing on average two pseudo states per original HMM state the positioning error could be significantly reduced without increasing the training effort.

Zeitgenössische Praktiken von Subjektivierung. Konsumismus, Kybernetischer Kapitalismus und Repräsentationskritik in Anschluss an Tiqquns Figur der Jungen-Mädchen - Degeling, Jasmin (onlinejournal kultur&geschlecht)

Rezension zu: Clemens Apprich / Felix Stalder (Hgg.): Vergessene Zukunft. Radikale Netzkulturen in Europa, Bielefeld: transcript 2012 - Schmitt, Martin (sehepunkte)

van Dalen, Dirk, L.E.J. Brouwer. Topologist, intuitionist, philosopher. How mathematics is rooted in life [updated revision of the two volume biography ‘Mystic, geometer, and intuitionist. The life of L.E.J. Brouwer’ published 1999 and 2005], Springer: Berlin 2013 - Peckhaus, Volker (zbMATH Open, Zbl. 1255.01024)

Edmund Husserl, Introduction to Logic and Theory of Knowledge. Lectures 1906/07, translated by Clair Otiz Hill, Springer: Dordrecht 2008 (Edmund Husserl, Collected Works, Bd. XIII) - Peckhaus, Volker (zbMATH Open, Zbl. 1255.01025)

Friederich, Simon, “Motivating Wittgenstein’s Perspective on Mathematical Sentences as Norms”, Philosophia Mathematica (3) 19 (2011), 1–19 - Peckhaus, Volker (zbMATH Open, Zbl. 1271.00015)

Sieg, Wilfried, Hilbert’s Programs and Beyond, Oxford University Press: Oxford 2013 - Peckhaus, Volker (zbMATH Open, Zbl. 1281.01004)

Purkert, Walter, “The Double Life of Felix Hausdorff/Paul Mongré”, The Mathematical Intelligencer 30, No. 4, 36–50 - Peckhaus, Volker (zbMATH Open, Zbl. 1254.01038)

Music Encoding Initiative Guidelines Version 2.1.0 - Kepper, Johannes; Roland, Perry D.

Musical Variants in Encoding, Analysis and Visualization - Kepper, Johannes; Roland, Perry D.; Röwenstrunk, Daniel (Proceedings of Balisage: The Markup Conference 2013)

Vorratsbomben im Himmel. Über digitalen Terror, unsichtbare Opfer und die Rhetorik der Präzision - Weber, Jutta (Heinrich-Böll-Stiftung: High-Tech-Kriege: Frieden und Sicherheit in Zeiten von Drohnen, Kampfrobotern und digitaler Kriegsführung)